A SYSTEMATIC LITERATURE REVIEW ON THE EFFECT OF MATH ANXIETY TOWARDS MATH PERFORMANCE AND ACHIEVEMENT - Anita Purnamasari (PT Akselerasi Karya Mandiri, 2023)
Anxiety is one of the factors that is believed to affect performance and achievement in learning subjects. However, the belief is still debatable. The fact that many students around the world consider that mathematics is a difficult subject. This study explores the effects of math anxiety towards math performance and math achievement. By understanding this connection, it is expected that the teacher will be able to take appropriate steps in teaching mathematics. This study used the Systematic Literature Review (SLR) method, 15 articles were sorted and selected based on the required criteria, the data taken from the Google Scholar database, within search strings from 2019 to 2023. The results showed some points that the math anxiety scales used depending on the participant's characteristics in each study, 8 main factors driving the emergence of math anxiety and math anxiety affects math performance and achievement, especially at higher grade levels.